Integration of Reversing Voltage Multilevel Inverter Topology with High Voltage Gain boost Converter for Distributed Generation - S. Nagaraja Rao; D. V. Ashok Kumar; Ch. Sai Babu (Institute of Advanced Engineering and Science, 2018)
The conventional energy sources available to us are on the verge of depletion. This depletion of conventional energy source leads to concentrate more on alternative energy sources. In this research, the focus is on the role of renewable energy sources (RES) in electrical power generation. Even though, the RES based plants produce power, we cannot directly connect it to the grid or loads. Because, the voltage ratings and nature supply of RES plants would not match with the load. Hence, this is a major issue for connecting RES plants to load or other utility. The power electronic converters are extensively being used as a link between load and supply. As most of the renewable energy power generation is DC in nature, the DC-DC converter is used to increase the voltage level and this DC must be converted to AC for grid connection. Therefore, inverters are used for DC to AC conversion. In this paper, the DC supply of renewable energy is connected to load by using cascade DC-DC converters along with a proposed reversing voltage (RV) multilevel inverter (MLI). The first DC-DC converter is used to enhance the voltage level with high gain and second converter is used to split the DC supply for inverter convenience. In this paper, proposed RV symmetrical and asymmetrical MLI generates 7, 9, 11, 13 and 15 levels with only ten power switches. In-phase level-shifted triangular carrier type sine pulse width modulation (PWM) technique is employed to trigger the commutating switches of proposed RV MLI. Switches of H-Bridge for reverse voltage appearance across the load are triggered by simple pulse generator. The circuits are modeled and simulated in MATLAB/SIMULINK software. Results are presented and discussed.